Deletion analysis of Duchenne muscular dystrophy - Erdem, Hayat; Ayter, Şükrüye; Özgüç, Meral; Topçu, Meral; Topaloğlu, Haluk; Renda, Yavuz (The Turkish Journal of Pediatrics, 1993)
DNA of 15 patients with Duchenne muscular dystrophy (DMD) were analyzed for deletions within the DMD gene by using recombinant DNA technology. Deletion frequency was 47 percent and six of the deletions occurred in the region of probe 7 + 8. Only one of the deletions was observed in the region of probe 9-7, and no deletions were found in the regions of probe 30-1, 30-2 and 47-4 (5b + 6). The frequency of deletions found in the Turkish DMD patients corresponds to frequencies reported for other populations.